2015
DOI: 10.1096/fj.14-267575
|View full text |Cite
|
Sign up to set email alerts
|

Men and women differ in their diurnal expression of monocyte peroxisome proliferator‐activated receptor‐α in the fed but not in the fasted state

Abstract: Peroxisome proliferator-activated receptor-a (PPARa) plays a pivotal role in regulating metabolic response to fasting and is an inhibitor of inflammatory pathways in immune cells. It represents a therapeutic target for treatment of several diseases, mainly hyperlipidemia. To shed light on PPARa expression changes in response to fasting, young healthy male and female volunteers were fed or fasted for 24 hours. Monocytes were analyzed every 2 hours to compile both profiles of mRNA and protein expression of PPARa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The data in Figure suggest that sex differences in PPARα are involved in sex differences in hypertrophy. This hypothesis would be consistent with data showing sex differences in the regulation of PPARα . Of note in PPARα‐knockout mice, inhibition of carnitine palmitoyltransferase I resulted in death of 100% of the male mice but only 25% of the female mice, suggesting sex differences in the response to changes in PPARα .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The data in Figure suggest that sex differences in PPARα are involved in sex differences in hypertrophy. This hypothesis would be consistent with data showing sex differences in the regulation of PPARα . Of note in PPARα‐knockout mice, inhibition of carnitine palmitoyltransferase I resulted in death of 100% of the male mice but only 25% of the female mice, suggesting sex differences in the response to changes in PPARα .…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis would be consistent with data showing sex differences in the regulation of PPARa. [61][62][63] Of note in PPARa-knockout mice, inhibition of carnitine palmitoyltransferase I resulted in death of 100% of the male mice but only 25% of the female mice, suggesting sex differences in the response to changes in PPARa. 64 We reasoned that if PPARa mediates the sex difference in hypertrophy, elimination of sex differences in PPARa using an acute 3-week treatment with an inhibitor should block the sex differences in the development of hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estrogen replacement therapy in women in a specific time window is associated with reduced incidence of AD (reviewed in [269]). Although no differences in PPARα expression were reported between men and women in skeletal muscles [270], several studies indicate that human circulating mononuclear and T cells exhibit sex differences driven by the expression of PPARα and PPARγ [271,272]. In their study, Zhang et al showed that the treatment of T cells with androgens increases PPARα and decreases PPARγ expression [272].…”
Section: Pparα and Sexmentioning
confidence: 99%
“…In our model, undernutrition was initiated during the second week of life; it remains to be determined whether increased SIRT1 expression would cause PPARα deacetylation and degradation if malnourishment was initiated after mice reached adulthood. Sex differences in PPARα expression recently were reported in human monocytes ( 39 ). In addition to the known interactions between estrogen and PPARα transcriptional activity ( 40 ), sexual dimorphism of PPARα protein levels could have important implications for sex differences in the frequency of metabolic disorders and their treatment ( 41 ).…”
Section: Discussionmentioning
confidence: 98%